Characterising radium-226 particles from legacy contamination to support radiation dose assessments. (February 2020) - McGuire, C.; Dale, P.; Copplestone, D.; Wilson, C.; Tyler, A.
Abstract: Radioactive particles are physically discrete sources of radioactivity that have been released into the environment as a result of past emergencies, events and practices. As the release of radioactive particles is often unplanned, the source term has not been characterised, and the potential radiation doses have not been prospectively assessed. If a plausible exposure pathway exists, radioactive particles in the environment may present a hazard to the public depending on their radiological, physical and chemical characteristics. Given their physically discrete nature, standard assessment approaches such as dispersion and transfer modelling of liquid and gaseous radioactive releases, are not appropriate for radioactive particles. The challenge for national regulatory authorities is to calculate potential radiation doses from unplanned releases of radioactive particles into the environment, assess whether the doses are relevant to radiological protection and decide whether actions are required to reduce potential doses. To address this challenge, this paper presents the approach being adopted to radiologically, physically and chemically characterise Ra-226 particles from a contaminated legacy site using gamma spectrometry, optical macroscopy and SEM-EDS. The use of particle characterisation data to support radiation dose assessments is discussed and consideration is given to radioactive particles in the context of radiological protection. Highlights: Particle characterisation data required to support dose assessments is presented. Radiological, physical and chemical characterisation of Ra-226 particles is ongoing. Characterisation data for one Ra-226 particle is presented as an example. Plan to use Ra-226 particle characterisation data in dose assessments is discussed. A new radioactive particle definition is needed to support dose assessments.